2018
DOI: 10.31234/osf.io/bqa5v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stable individual differences in strategies within, but not between, visual search tasks

Abstract: A striking range of individual differences has recently been reported in three different visual search tasks. These differences in performance can be attributed to strategy, that is, the efficiency with which participants control their search to complete the task quickly and accurately. Here we ask if an individual's strategy and performance in one search task is correlated with how they perform in the other two. We tested 64 observers in the three tasks mentioned above over two sessions. Even though the test-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…In the hunted condition, it would be necessary to keep a safe distance between the sheep and the nearest wolf and at all times, to avoid being eaten and cancelling the trial. Finally, a consistent finding in many previous studies from our group, and other labs, has been the existence of subsets of individuals who continue to forage randomly under conjunction conditions (e.g., Clarke et al, 2018;Jóhannesson et al, 2017;Á. Kristjánsson et al, 2014;Tagu & Kristjánsson, 2020; We termed these individuals "super-foragers" as they seemed immune to the increase in attentional load (Watson & Strayer, 2010).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In the hunted condition, it would be necessary to keep a safe distance between the sheep and the nearest wolf and at all times, to avoid being eaten and cancelling the trial. Finally, a consistent finding in many previous studies from our group, and other labs, has been the existence of subsets of individuals who continue to forage randomly under conjunction conditions (e.g., Clarke et al, 2018;Jóhannesson et al, 2017;Á. Kristjánsson et al, 2014;Tagu & Kristjánsson, 2020; We termed these individuals "super-foragers" as they seemed immune to the increase in attentional load (Watson & Strayer, 2010).…”
Section: Resultssupporting
confidence: 78%
“…While we had initially pursued the idea that the ability to switch easily during conjunction foraging reflected stable individual differences in more general cognitive abilities, such as WM or attention span, the story appears to be more complex. For example, while such links between foraging ability and cognitive measures have been found in children (Ólafsdóttir et al, 2016, 2019), this is not the case with adults (Clarke et al, 2018;Jóhannesson et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…This finding suggests that the extended run behavior found in our original work [24]which has been replicated a number of times, both by our group [50][51][52] and others [53][54][55][56]does not rely exclusively on the feature/conjunction manipulation. Rather, it implies that this manipulation interacts with other aspects of the task design and/or display characteristics to constrain foraging behavior.…”
Section: Summary and Future Directionssupporting
confidence: 75%
“…This may prove useful in terms of identifying underlying mechanisms. For example, while previous studies with children have found clear links between foraging behavior and other, more general cognitive abilities (Ólafsdóttir et al, 2016, 2019), this has not been the case with studies of adults (Clarke et al, 2018;Jóhannesson et al, 2017).…”
Section: Discussionmentioning
confidence: 90%